2013
DOI: 10.1136/bmjopen-2013-002710
|View full text |Cite
|
Sign up to set email alerts
|

Lay perspectives of successful ageing: a systematic review and meta-ethnography

Abstract: ObjectivesThe aim of the current study was to conduct a systematic review of lay perspectives of successful ageing (SA), synthesise these data using a metaethnographic framework and to provide a snapshot of extant lay perspectives of SA.DesignA systematic review of layperson perspectives of SA was conducted across MEDLINE, PsycInfo, CINAHL, EMBASE and ISI Web of Knowledge.ParticipantsPeer-reviewed studies conducting qualitative investigations of lay perspectives of SA were included. Included studies were coded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
134
2
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 45 publications
18
134
2
13
Order By: Relevance
“…In order to preserve self-esteem, the old-old might better adopt worldviews that emphasize alternative resources for self-esteem and meaning in old age, alongside the acceptance of the inevitable deterioration in old age (Cosco et al 2013;Kahana et al 2012) (see Fig. 4.1).…”
Section: Discussionmentioning
confidence: 99%
“…In order to preserve self-esteem, the old-old might better adopt worldviews that emphasize alternative resources for self-esteem and meaning in old age, alongside the acceptance of the inevitable deterioration in old age (Cosco et al 2013;Kahana et al 2012) (see Fig. 4.1).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of operational definitions of successful ageing, Cosco et al (2014a) revealed more than 100 unique operationalisations. A subsequent systematic review by the same authors revealed that these perspectives of successful ageing from researchers did not align with those of older adults themselves (Cosco et al 2013(Cosco et al , 2014b. Laypersons suggest that a focus on psychosocial components -or more subjective components -are integral to healthy ageing whilst researchers focused more on biomedical -or more objective -components.…”
Section: Healthy Ageingmentioning
confidence: 99%
“…20 Most studies that were identified in our reviews had limited or low service user involvement in intervention development. Although much research has been undertaken with general older populations exploring their perspectives on successful ageing, 174 we did not identify any qualitative studies of older adults with mild frailty, eliciting their views on promoting health and well-being in the context of experiencing symptoms of frailty (e.g. lack of energy, feeling 'slowed up').…”
Section: Intervention Development: Identifying Effective Content For mentioning
confidence: 99%